Integrated Approach for a Knowledge-Based Process Layout for Simultaneous 5-Axis Milling of Advanced Materials. (23rd June 2011) - Klocke, F.; Bergs, T.; Busch, M.; Rohde, L.; Witty, M.; Cabral, G. F.
Abstract : Advanced materials, like nickel-based alloys, gain importance in turbomachinery manufacturing, where creating complex surfaces constitute a major challenge. However, milling strategies that provide high material removal rates at acceptable tooling costs demand optimized tool geometry and process parameter selection. In this paper, a description of circular milling is given, focusing on resulting engagement conditions. Regarding this, a test bench was designed to investigate the chip formation process in an analogy milling process. Furthermore, the methodology for the approach in the analogy process was developed. Results of a first test run in Inconel 718 verify the presented approach.